Availability of phosphorus in Ultisols by applying compost and phosphate rock - Jayadi, Muhammad; Rismaneswati, Rismaneswati; Majid, Sharini Abd (Anjoro: International Journal of Agriculture and Business, 2023)
Ultisols are the largest order in Indonesia among other acid soils, namely around 41,919 million ha, with the problem of insufficient P availability in soil for plant growth, requiring special treatment to increase available P in the soil. This study aims to examine the effect of compost and rock phosphate in increasing the availability of P in Ultisols. The research was conducted in April–May 2016 at the Laboratory of Chemistry and Soil Fertility, University of Hasanuddin, Makassar. The study used a randomized block design and was carried out by incubating straw compost, gamal leaves, cow dung and rock phosphate in Ultisol soil with a soil weight of 300 g. The research results show that 15th day of incubation showed the highest available P of 12.97 ppm with a pH of 5.15 in the KJ575%+KS525%+BF treatment, while on the 30th day of incubation the available P increased 17.45 ppm in the rock phosphate treatment with a pH of 5.58. The application of rock phosphate and SP36 reduced Al-P, Fe-P, and Ca-P, while the application of organic matter, in this case compost, did not reduce Al-P, Fe-P, and Ca-P.